Attitudes towards sex workers: a nationwide cross-sectional survey among German healthcare providers - Langenbach, Benedikt P.; Thieme, Andreas; van der Veen, Raquel; Reinehr, Sabrina; Neuendorff, Nina R. (Frontiers in Public Health, 2023)
Background: Worldwide, sex workers face stigmatization and discrimination, also within healthcare. Only few studies on healthcare providers' attitudes towards care of sex workers have been performed. This study assessed attitudes and knowledge of healthcare providers in Germany towards sex workers and their specific health risks. Methods: German healthcare professionals and medical students were invited to participate in a nationwide cross-sectional study in 2022. The online survey used a German translation of the 'Attitudes towards Prostitutes and Prostitution Scale' by Levin and Peled for assessment of attitudes towards sex work and workers, together with prevalence estimates of common mental and physical disorders. Results: A total of 469 questionnaires was included into analysis. Older participants tended to regard sex work as less of a choice (p<0.004) and sex workers as more victimized (p<0.001). The frequency of professional contact to sex workers neither affected the perception of sex workers' status as victims vs. independent individuals, nor the perceived moral status. Moreover, healthcare This is a provisional file, not the final typeset article professionals overestimated the prevalence of various disorders which was influenced by participants' attitudes towards sex workers. Discussion: A comparison to a recent Allensbach survey demonstrated similar attitudes of healthcare providers and the general population towards sex workers. Our results suggest that German healthcare professionals are not free of prejudices against sex workers, as has been shown for other marginalized groups in society. Instead, they seem to be influenced by personal opinion rather than by objective facts which they should have acquired during their professional education. Future interventions (e.g., better training regarding marginal societal groups) are necessary to encounter these issues in order to improve healthcare for sex workers.